2011
DOI: 10.1346/ccmn.2011.0590106
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ruthenium from Aqueous Solution by Clinoptilolite

Abstract: Ruthenium compounds are highly toxic and carcinogenic. In the present study, clinoptilolite was used in the removal of Ru species from aqueous solutions. Clinoptilolite is a good choice of sorbents because it is naturally abundant and therefore cheap. After the process where Ru was removed from the aqueous solution, the clinoptilolite was characterized by X-ray diffraction, X-ray fluorescence, thermogravimetric analysis, and Fourier-transform infrared spectroscopy techniques. The influence of pH, contact time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The adsorption of ruthenium (III) on graphene oxide is mainly attributed due to electrostatic attraction between the negative surface of graphene oxide bearing oxygen functional groups and ruthenium (III) ion and coordination of ruthenium (III) with oxygen atom. The attachment of hydroxyl group into ruthenium (III) coordination sphere reduces the interaction between ruthenium (III) and graphene oxide bearing surface negative charge on oxygen atom beyond pH 2 [31] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of ruthenium (III) on graphene oxide is mainly attributed due to electrostatic attraction between the negative surface of graphene oxide bearing oxygen functional groups and ruthenium (III) ion and coordination of ruthenium (III) with oxygen atom. The attachment of hydroxyl group into ruthenium (III) coordination sphere reduces the interaction between ruthenium (III) and graphene oxide bearing surface negative charge on oxygen atom beyond pH 2 [31] …”
Section: Resultsmentioning
confidence: 99%
“…The attachment of hydroxyl group into ruthenium (III) coordination sphere reduces the interaction between ChemistrySelect ruthenium (III) and graphene oxide bearing surface negative charge on oxygen atom beyond pH 2. [31] To investigate the effect of ionic strength, adsorption experiments were carried out with NaCl and MgCl 2 in the concentration range of 0.01-0.1 M. Figure 4 depicts the plot of adsorption capacity of ruthenium (III) on GO as a function of ionic strength. Experimental results revealed that, in case of NaCl, adsorption capacity decreases gradually with increase in NaCl concentration up to 0.07 M, beyond which it is independent of ionic strength.…”
Section: Effect Of Ph and Ionic Strengthmentioning
confidence: 99%